A produção do conhecimento em História da Educação nos Programas de Pós-Graduação em Educação das Universidades do Paraná (1984-2020) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
The present research is a historiography study aimed at analyzing the production of knowledge in the History of Education within the Graduate Programs in Education at eight universities in Paraná (UFPR, UEM, UEPG, UEL, UNIOESTE, UNICENTRO, PUC PR, and UTP). To achieve this, the main characteristics of the theses and dissertations defended will be investigated, analyzing themes, objects, research problems, theoretical frameworks, sources, periods, and locations studied, while seeking to identify the relationship between the developed research, the trajectories of the supervising professors, and their networks of sociability through research groups and the graduate programs where they worked. The temporal scope is justified according to the objects and sources of this research; thus, it was delimited to the year 1984, which marks the first defense of a dissertation in the History of Education in the Graduate Program in Education of a university in the state, and to 2020, which corresponds to the last year of defense and publication of academic works before the start of this research. The theoretical framework is based on Pierre Bourdieu's contributions regarding the concepts of field, agent, trajectory, habitus, and capital, as well as specific authors in the History of Education, such as Bastos, Bencostta, and Cunha (2004; 2005), Bittar (2006; 2019), Bontempi Junior (1995; 2012; 2019), Catani and Faria Filho (2002; 2005), Gatti Junior (2015; 2017), Nunes (1995; 1996; 2005; 2006), Saviani (1998; 2008; 2009; 2015), Vieira and Gondra (2005), Warde (1984; 1990; 1995), among others. The research is of a quantitative and qualitative nature and involves bibliographic and documentary research. Initially, the research to be analyzed were selected based on abstracts and introductions that encompassed the History of Education. Subsequently, based on the information gathered from these researches, the researching professors who supervised these studies were identified. Finally, an analysis of the researches was conducted, relating them to the trajectory and work of the researchers to understand the characteristics of the research developed at each university. This thesis argues that the production of knowledge about the history of education in Paraná is characterized by the organization, structure, and practices developed in its places of production, that is, according to the work of the supervising professors and graduate students, mainly organized in research groups, and the structure of the programs, according to their areas of concentration and research lines. Thus, the characteristics of the research are related to the configurations of the research field and the habitus shared by the agents involved in the development of the works. However, we emphasize that the field is heterogeneous, and although there are predominant research characteristics, there are also non-hegemonic characteristics that help compose the field. In this sense, we seek to highlight throughout the work the differences that permeated the institutions, courses, research groups, and the work of the professors, impacting the diversity of the research. Throughout the work, the main characteristics of each university regarding the production of knowledge in the History of Education in Graduate Programs in Education will be emphasized. In summary, this research aims to contribute to studies in the History of Education in Paraná, aiming to answer the following question: How is the production of knowledge in the History of Education characterized in the research developed by the Graduate Programs in Education at the universities in Paraná, based on the theses and dissertations defended? In addition to this central question, another complementary question arises: Who are the researching professors involved in these studies, and how do their trajectories and networks of sociability impact knowledge production? Thus, this thesis aims to contribute to the field of the history of education by showing the main research trends and identifying gaps in the field that can be analyzed in future research.
Keywords: Campo acadêmico; História da Educação; Historiografia; Programa de Pós- Graduação em Educação; Universidades do Paraná; Academic field; Graduate Program in Education; History of Education; Historiography; Universities of Paraná; CNPQ::CIENCIAS HUMANAS::EDUCAÇÃO